Oxygen Toxicity and Special Operations Forces Diving: Hidden and Dangerous - Wingelaar, Thijs T.; van Ooij, Pieter-Jan A. M.; van Hulst, Rob A. (Frontiers in Psychology, 2017)
In Special Operations Forces (SOF) closed-circuit rebreathers with 100% oxygen are commonly utilised for covert diving operations. Exposure to high partial pressures of oxygen (PO2) could cause damage to the central nervous system and pulmonary system. Longer exposure time and higher PO2 leads to faster development of more serious pathology. Exposure to a PO2 above 1.4 ATA can cause central nervous system toxicity, leading to a wide range of neurologic complaints including convulsions. Pulmonary oxygen toxicity develops over time when exposed to a PO2 above 0.5 ATA and can lead to inflammation and fibrosis of lung tissue. Oxygen can also be toxic for the ocular system and may have systemic effects on the inflammatory system. Moreover, some of the effects of oxygen toxicity are irreversible. This paper describes the pathophysiology, epidemiology, signs and symptoms, risk factors and prediction models of oxygen toxicity and their limitations on SOF diving.